Managerial multitasking in the mutual fund industry - Vikas Agarwal; Linlin Ma; Kevin Mullally (University of Cologne, Centre for Financial Research (CFR), 2015)
We examine the determinants and consequences of mutual fund managers simultaneously managing multiple funds. Well-performing managers multitask by taking over poorly performing funds or launching new funds. Subsequent to multitasking, funds run by managers prior to multitasking (i.e., incumbent funds) experience performance deterioration while the performance of the acquired funds improves. Multitasking increases the assets of fund companies but results in a wealth transfer from shareholders of the incumbent funds to those of the funds the managers take over. Multitasking arrangements are terminated when investors recognize the associated agency problem and withdraw their capital from the incumbent funds.
Keywords: G10; G20; G23; 330; Multitasking; Fund Performance; Fund Flows; Agency Problems